Model-driven DevOps increasing agility and security in your physical network through DevOps - Carter, Steven; King, Jason; Lothian, Josh; Younkers, Mike (Addison-Wesley, 2023)
Using Model-Driven DevOps and the Infrastructure as Code (IaC) paradigm, IT teams can develop and operate infrastructure more quickly, consistently, and securely than ever beforegrowing agility, getting to market sooner, and delivering more business value. Now, four leading practitioners walk you step by step through successfully implementing Model-Driven DevOps. Drawing on deep hands-on experience, they share lessons learned, present solutions to common pitfalls, and illuminate crucial differences between DevOps for infrastructure and the application-based DevOps most books cover. This relentlessly practical guide shows developers and operators how to work together in tailoring its detailed, prescriptive approach to infrastructure, and how to address the human and organizational issues that cause some organizations to fail. You'll learn how to create SDN and IaC data models to manage massive numbers of network elements, organize enormous quantities of network data, and apply DevOps to infrastructure repeatably and consistently. The authors' deep dive into Model Driven DevOps includes use cases and specific examples, supported with sample open source code in their companion code repositories.
Includes index
Keywords: Computer software -- Development; Software engineering; Génie logiciel; Computer software; Development